2022
DOI: 10.2465/jmps.220309
|View full text |Cite
|
Sign up to set email alerts
|

Platinum–group minerals in the placer deposit in northwestern Hokkaido, Japan: description of a new mineral, tomamaeite

Abstract: Mineralogical investigation of platinum-group minerals (PGM) from the placer deposit in northwestern Hokkaido, Japan, was conducted at six rivers and two coasts covering an area of 70 km north-south and 30 km east-west: the Moshosanbetsu River (M), the Shosanbetsu River (S), the Ainusawa River (A), the Tomamae coast (T), the Obira coast (OC), the Kamikinenbetsusawa River (K), the Obirashibe River (OR), and the Numatapon River (N) from north to south. Details of the major PGM grain and the occurrence of small b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The Pt-based alloy grains were composed of isoferroplatinum although the rims of these grains had occasionally been transformed into tulameenite or tetraferroplatinum. Nishio-Hamane and Saito (2022) previously demonstrated that such grains can contain a variety of inclusions by SEM observation for a cross section of a sample. The present study also reports the discovery of ezochiite inclusions.…”
Section: A C C E P T E D I N J M P S P R E -P R O O Fmentioning
confidence: 97%
See 4 more Smart Citations
“…The Pt-based alloy grains were composed of isoferroplatinum although the rims of these grains had occasionally been transformed into tulameenite or tetraferroplatinum. Nishio-Hamane and Saito (2022) previously demonstrated that such grains can contain a variety of inclusions by SEM observation for a cross section of a sample. The present study also reports the discovery of ezochiite inclusions.…”
Section: A C C E P T E D I N J M P S P R E -P R O O Fmentioning
confidence: 97%
“…The sampling sites employed in the present study are in northwestern Hokkaido, representing the same region previously examined by Nishio-Hamane and Saito (2022). This area included the Moshosanbetsu river, the Shosanbetsu river, the Ainusawa river, the Tomamae coast, the Obira coast, the Kamikinenbetsusawa river, the Obirashibe river and the Numatapon river.…”
Section: A C C E P T E D I N J M P S P R E -P R O O Fmentioning
confidence: 99%
See 3 more Smart Citations